2013
DOI: 10.1890/12-1752.1
|View full text |Cite
|
Sign up to set email alerts
|

Fire history, related to climate and land use in three southern Appalachian landscapes in the eastern United States

Abstract: Fire-maintained ecosystems and associated species are becoming increasingly rare in the southern Appalachian Mountains because of fire suppression policies implemented in the early 20th century. Restoration of these communities through prescribed fire has been hindered by a lack of information on historical fire regimes. To characterize past fire regimes, we collected and absolutely dated the tree rings on cross sections from 242 fire-scarred trees at three different sites in the southern Appalachian Mountains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 78 publications
7
47
1
Order By: Relevance
“…MFIs did not differ statistically between sites or time periods, except for the pre-European and European settlement time periods at SGL 107 (Table 1). During the pre-European time period, SGL 107 had two significantly long fire intervals (1664-1701, 1701-1729; Figure 3); interestingly, both The fire frequencies reported here are comparable to those of two previous studies conducted in yellow pine forests of the Ridge and Valley Province [65,66], located approximately 750 and 420 km to the south, respectively. Another study, also to the south, but closer (approximately 180 km) on the Appalachian Plateau, also reported similar fire frequencies from white oaks [67].…”
Section: Fire Frequencysupporting
confidence: 85%
“…MFIs did not differ statistically between sites or time periods, except for the pre-European and European settlement time periods at SGL 107 (Table 1). During the pre-European time period, SGL 107 had two significantly long fire intervals (1664-1701, 1701-1729; Figure 3); interestingly, both The fire frequencies reported here are comparable to those of two previous studies conducted in yellow pine forests of the Ridge and Valley Province [65,66], located approximately 750 and 420 km to the south, respectively. Another study, also to the south, but closer (approximately 180 km) on the Appalachian Plateau, also reported similar fire frequencies from white oaks [67].…”
Section: Fire Frequencysupporting
confidence: 85%
“…Land use change, including a reduction in grazing activities, and a decrease in population density coincided with fire cessation in this mountain landscape. Farther south at sites in the Blue Ridge Mountains of North Carolina and in the Ridge and Valley and Blue Ridge physiographic regions of eastern Tennessee, fire cessation dates were in the 1950s, 1960s, and 1930s, respectively (Flatley et al 2013). In each case, it was shown that fires occurred regularly from the late 1700s through the end of the industrial logging era.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of anthropogenic fires throughout the fire record may have masked a stronger climate-fire association (McEwan et al 2007;Flatley et al 2013). Fire events generally occurred during dry years (see Figure 5a) and there was a significant association between drought and growth release events (Figure 5b), suggesting that fire was driven by periodic drought, in addition to early settlement and industrial activities.…”
Section: Discussionmentioning
confidence: 99%
“…and hickory (Carya spp.) [56,57]. Virginia pine (P. virginiana) is locally common, especially in xeric, low elevation sites that are regenerating from past agricultural clearing.…”
Section: Study Areamentioning
confidence: 99%